Hospitalization Costs and Duration for Preterm and Low Birth Weight Infants under National Health Insurance - Kurniawan, Farhan; Yulianty Permanasari, Vetty; Nadjib, Mardiati; Chandra Nugraha, Erfan (Jurnal Jaminan Kesehatan Nasional, 2025)
Preterm birth and low birth weight are major contributors to neonatal morbidity, mortality, and healthcare costs in Indonesia. This study investigates how maternal risk factors and hospital characteristics jointly influence length of stay and inpatient costs for preterm and low birth weight infants covered by the national health insurance program (JKN) in 2022–2023. Using a retrospective cohort of administrative claims data and multilevel generalized linear models, we find that younger maternal age, neonatal complications, and concurrent diagnoses of prematurity and low birth weight significantly increase both length of stay and costs. Infants from non-government-subsidized members group (PBI – Penerima Bantuan Iuran) and those admitted to referral or public hospitals experience longer stays, while regional tariff differences and hospital ownership shape cost variations. By linking maternal risk, facility capacity, and financial burden under Indonesia’s case-based payment system (INA-CBGs – Indonesia Case-Based Groups), this study highlights pathways to improve neonatal care efficiency. Strengthening antenatal services and referral systems may help reduce avoidable admissions and optimize resource use.